Functional Dilemma

Algebra Level 3

Suppose that f ( n + 1 ) = f ( n ) + f ( n 1 ) f(n+1) = f(n) + f(n-1) for n = 1 , 2 , 3 , n=1,2,3,\ldots . If f ( 6 ) = 2 f(6) = 2 and f ( 4 ) = 8 f(4) = 8 , what is the value of f ( 3 ) + f ( 5 ) f(3) + f(5) ?


The answer is -20.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Too small...

A Former Brilliant Member - 5 years, 5 months ago

Log in to reply

Sorry. I rushed to give a solution for this haha

Russel Ryan Floresca - 5 years, 5 months ago

Did you get the correct answer?

Russel Ryan Floresca - 5 years, 5 months ago

Log in to reply

Yes, I did, with a similar method.

A Former Brilliant Member - 5 years, 5 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...